PENGARUH BRAND AMBASSADOR DAN REVIEW PRODUCT TERHADAP KEPUTUSAN PEMBELIAN SEPATU VENTELA DI MARKETPLACE SHOPEE - Zahid, Muhammad Marzuki; Marlena, Novi (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
Abstract Consumers have a high tendency to buy products on Shopee e-commerce. When deciding to buy, consumers will choose the most suitable product by considering product reviews and brand ambassadors. This study aims to analyze the influence of brand ambassadors (X1) and product reviews (X2) on the decision to buy Ventela shoes on the Shopee marketplace. Primary data was obtained through a questionnaire, the distribution was carried out by a google questionnaire form filled out by 120 respondents who were Shopee users and had purchased Ventela shoes. Data analysis was carried out with a descriptive quantitative approach using multiple linear regression with the SPSS application. The results of this study show that brand ambassadors and product reviews have an influence on the decision to buy Ventela shoes on the Shopee marketplace. The practical implication of this study is that companies can choose the appropriate brand ambassadors, paying attention to product reviews because consumers use product reviews to consider purchase decisions. For researchers with related titles, it is expected to add product quality variables because these variables will affect purchasing decisions.